Assessment of Combined Karyotype Analysis and Chromosome Microarray Analysis in Prenatal Diagnosis: A Cohort Study of 3710 Pregnancies. (29th December 2022) - Wang, Jin; Wang, Danni; Yin, Yan; Deng, Yi; Ye, Mengling; Wei, Ping; Zhang, Zhuo; Chen, Chun; Qin, Shengfang; Wang, Xueyan
Abstract : Objective . The current study aimed to compare the characteristics of chromosome abnormalities detected by conventional G-banding karyotyping, chromosome microarray analysis (CMA), or fluorescence in situ hybridization (FISH)/CNVplex analysis and further explore the application value of combined karyotype analysis and CMA in prenatal diagnosis with a larger sample size. Methods . From March 2019 to March 2021, 3710 amniocentesis samples were retrospectively collected from women who accepted prenatal diagnosis at 16 to 22 + 6 weeks of pregnancy. The pregnant women underwent karyotype analysis and CMA. In the case of fetal chromosomal mosaicism, FISH or CNVplex analysis was utilized for validation. Results . In total, 3710 G-banding karyotype results and CMA results from invasive prenatal diagnosis were collected. Of these, 201 (5.41%) fetuses with an abnormal karyotype were observed. The CMA analysis showed that the abnormality rate was 9.14% (340/3710). The detection rate of CMA combined with karyotype analysis was 0.35% higher than that of CMA alone and 4.08% higher than that of karyotyping alone. Additionally, 12 cases had abnormal karyotype analysis, despite normal CMA results. To further detect the chromosome mosaicism, we used FISH analysis to correct the karyotype results of case 1. Correspondingly, a total of 157 cases showed abnormal CMA results but normal karyotype analysis. We also found chromosomal mosaicism in 4 cases using CMA. Moreover, CNVplex and CMA demonstrated that representative case 15 was mosaicism for trisomy 2. Conclusions . Conventional G-banding karyotyping and CMA have their own advantages and limitations. A combination of karyotype analysis and CMA can increase the detection rate of chromosome abnormalities and make up for the limitation of signal detection.